A study on customer awareness and perception toward hydroponics’ / Zaira Mohd Rosilan - Rosilan, Zaira Mohd (2009)
This survey studies the way in customer awareness and perception toward hydroponics’ Hydroponics (from the Greek words hydro water and ponos labor) is a method of growing plants using mineral nutrient solutions, without soil. If a plant is grown without soil and with a complete nutrient solution, that's hydroponics! Customer awareness and perception is a process by which an individual selects, organizes and interprets stimuli into a meaningful and coherent picture of the world. It can be described as “how we see the world around us”. Independent variables factor that may lead customer awareness and perception are quality, value, brand, image and promotion. Consumers’ perceptions are much more important than their knowledge of objective reality. For the purpose of this study, the researcher has adopted the descriptive research design due to it’s used to descriptive research design through survey method. The survey method involves a structured questionnaire given to respondents and designed to elicit specific information. Target population is around Malacca and 100 questionnaires will use by done non – probability sampling technique. For collection data, will use both technique which primary data and secondary data. This study reliable and acceptable because the reliability statistics is 0.749. Customers do not fully aware on the concept of hydroponics’ which have difference understanding about hydroponics’ and come out difference perception.